Cartoon Posters as a Learning Media for Students’ English Vocabulary Achievement at PAUD Al-Assrye, Bogor - Wijayanti, Sheila; Zulha, Hani Fatimah; Muhjaj, Juniya Bintang (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2025)
In the era of globalization, English has become an international language used in almost all aspects of life, connecting individuals and conveying information globally. Many schools have emerged for children aged 2-6 years, with various adequate facilities that support the development of children's sensory motor skills and bilingual or trilingual languages of instruction used in class as communication support. Physical and psychosocial development is needed at the kindergarten stage, including intellectual, language, motor, and social-emotional development. In addition, mastery of the English vocabulary taught will support growth at the next level. More extra socialization is needed in learning, especially introducing English vocabulary. The method used in this activity is a silent way, which has several steps, namely socialization, demonstration, and practice with media and evaluation. The result of this activity can be seen from the graph showing an increase in participants' English vocabulary skills. Of the total students of PAUD Al-Assrye Bogor in class TK A, there are 15 people. In the initial percentage before this socialization activity occurred, only around 26,7%, namely four students, understood English vocabulary about parts of body. Then, 73,3% namely eleven students, not understood English vocabulary about parts of body. Then, after this activity, the percentage results increased to 66,7%, namely ten students who understood English vocabulary about parts of body. Then, 33,3%, namely five students who only confused English vocabulary about parts of body. The data shows that 40% of students experienced an increase in their ability to understand the English vocabulary taught. So, the kindergarteners at PAUD Al-Assrye, Bogor, experienced increased English vocabulary knowledge that can be used for further education levels by using learning media, namely cartoon posters. It is because the cartoon posters used have various colours that attract students' attention and concentration so that students can focus on the media provided.